Map of Earthquake Prone Areas Using Geographic Information Systems(Peta Daerah Rawan Gempa Menggunakan Sistem Informasi Geografis) - Rafki Imani; Heri Yanto (Jurnal KomtekInfo, 2019)
This study aims to map the earthquake prone areas, and identify the nearest alternative route for evacuation of earthquake victims in Singkarak District, Solok Regency, West Sumatra. This research method was conducted with descriptive methods that analyzed by GIS (Geographic Information System) based on intensity scale (MMI). The results of this study stated that 90% of villages in Singkarak District had a high earthquake intensity, with an acceleration of the land surface of more than 0.34 g. For evacuation areas can be directed away from areas with steep cliffs and areas close to high buildings and should be directed in the direction close to Lake Singkarak, because the area around this has a low earthquake risk with earthquake acceleration of only 0.1 g.